Gestão estratégica de compras em uma empresa do segmento de material escolar : estudo de caso longitudinal - Senapeschi Neto, Alberto (Universidade Federal de São Carlos, 2008)
In the last years, some expressions such enterprises and supplier cooperation relationship have became used. The main objective of those relationships is to improve the competitiveness of the organizations through costs reductions and quality / flexibility improvements. On this context, this work presents and analyzes, through a case study method, a new form of purchasing management in a stationery products company that is the Brazilian leader of its segment. The enterprise looks for a higher organizational strategy alignment in order to guarantee its leadership. To achieve this aim, the enterprise changed its manufacturing management framework, initially based just on cost and quality issues, to a more responsive paradigm. The work presents all changes inside the purchasing department and the consequent effects to other areas directly related to the acquisition process. A theoretical and empiric analyses is presented, where the research, based on theory, identify the main manufacturing management strategic paradigms and how they can be related to the state of art in purchasing management. Following, the work presents the purchasing management framework of the organization in two different moments: from 1998 to 2001 and after 2002. It will be possible to realize how strategic the purchasing management can become to an organization. The results can be useful to enterprises with the same characteristics or inserted in the same process of change.
Keywords: Gestão de suprimentos; Compras; Paradigmas estratégicos de gestão da manufatura; ENGENHARIAS::ENGENHARIA DE PRODUCAO